Mid-arm circumference, body fat, nutritional and inflammatory biomarkers, blood glucose, dialysis adequacy influence all-cause mortality in hemodialysis patients: A prospective cohort study. Issue 12 (March 2019) - Duong, Tuyen Van; Wu, Pei-Yu; Wong, Te-Chih; Chen, Hsi-Hsien; Chen, Tso-Hsiao; Hsu, Yung-Ho; Peng, Sheng-Jeng; Kuo, Ko-Lin; Liu, Hsiang-Chung; Lin, En-Tzu; Feng, Yi-Wei; Yang, Shwu-Huey
Abstract : Abstract: Hemodialysis patients are at the high risk for morbidity and mortality. Evaluation and management of body composition and biochemical values are important to improve dialysis outcomes. We aimed to examine the effects of the mid-arm circumference, body fat, nutritional and inflammatory biomarkers, blood glucose, and dialysis adequacy on the mortality. A prospective cohort study was conducted on 375 patients from 7 hospital-based dialysis centers. At baseline between September 2013 and April 2017, we assessed patients' characteristics using chart review, body composition using the bioelectrical impedance analysis, and biochemical parameters using available laboratory tests. Patients were followed-up for all-cause mortality until April 2018. Kaplan–Meier Curves with Log-rank test, and Cox proportional hazards models were used to analyze the effects of assessed factors on the mortality. During the median of follow-up time of 1.4 (1.0–3.2) years, 47 (12.5%) patients died. In the multivariate analysis, mid-arm circumference (hazard ratio, HR, 0.90; 95% confidence interval, 95%CI, 0.82–0.99; P = .036), body fat mass (HR, 0.95; 95%CI, 0.91–1.00; P = .031), percent body fat (HR, 0.96; 95%CI, 0.92–0.99; P = .024), serum creatinine (HR, 0.81; 95%CI, 0.68–0.96; P = .015), and eKt/V (HR, 0.07; 95%CI, 0.01–0.33; P = .001) reduced the mortality risk. Inflammation (HR, 2.90; 95%CI, 1.59–5.27; P < .001), hyperglycemia (HR, 2.16; 95%CI, 1.06–4.40; P = .033), and low serum uric acid (HR, 2.22; 95%CI, 1.15–4.31; P = .018) increased the death risk. In hemodialysis patients, the higher values of the mid-arm circumference, body fat, serum creatinine, uric acid, and dialysis adequacy were associated with lower mortality, whereas, inflammation and hyperglycemia associated with higher mortality.